Growth Kinetics and Sensing Features of Colloidal Silver Nanoplates. (15th January 2019) - Compagnini, Giuseppe; Condorelli, Marcello; Fragalà, Maria E.; Scardaci, Vittorio; Tinnirello, Ilaria; Puglisi, Orazio; Neri, Fortunato; Fazio, Enza
Abstract : This paper presents the growth mechanisms and the plasmon sensing features for a large class of silver nanoplates obtained in the colloidal form. The synthesis is conducted by seed-mediated growth and leads to plates with aspect ratios as large as 20, having localized surface plasmon resonances extending deeply into the infrared spectral region (1000 nm and above). We measure plasmon sensitivity by varying the colloidal local refractive index, andΔ λ / Δ n sensitivity values up to 500 nm/RIU are obtained. Theoretical considerations regarding the correlation between the refractive index sensitivity and the position of the main localized plasmon resonance band demonstrate that plasmon sensitivity does not depend directly on the nanoparticle shape and aspect ratio.